Free Higher Education: Mistaking Equality and Equity - de Gayardon, Ariane (International Higher Education, 2017)
Free higher education is seeing a revival of popularity globally at a time when students and their families are asked to contribute ever more toward the cost of college. However, contrary to popular belief, free-tuition higher education is not necessarily associated with better access to, or equity within, tertiary education. This article takes a closer look at the realities behind “free” higher education, more specifically in its relationship with access.